2023
DOI: 10.1111/epi.17490
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes after anterior temporal lobectomy and transsylvian selective amygdalohippocampectomy: A quantitative comparison of clinical and diffusion data

Abstract: Objective: Anterior temporal lobectomy (ATL) and transsylvian selective amygdalohippocampectomy (tsSAHE) are effective treatment strategies for intractable temporal lobe epilepsy but may cause visual field deficits (VFDs) by damaging the optic radiation (OpR). Due to the OpR's considerable variability and because it is indistinguishable from surrounding tissue without further technical guidance, it is highly vulnerable to iatrogenic injury. This imaging study uses a multimodal approach to assess visual outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…Pruckner et al adopted a multimodal approach to assess visual outcomes following epilepsy surgery. They presented clinical and neuroimaging evidence that suggested anterior temporal lobectomy (ATL) carried a greater risk and led to more severe postoperative VFDs compared to temporal selective amygdalohippocampectomy (tsSAHE) ( 69 ). Winston et al reported that incorporating optic nerve radiography during anterior temporal lobectomy (ATLR) for refractory temporal lobe epilepsy (TLE) had the potential to reduce the severity of postoperative VFDs without impacting seizure outcomes or hippocampal resection ( 70 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pruckner et al adopted a multimodal approach to assess visual outcomes following epilepsy surgery. They presented clinical and neuroimaging evidence that suggested anterior temporal lobectomy (ATL) carried a greater risk and led to more severe postoperative VFDs compared to temporal selective amygdalohippocampectomy (tsSAHE) ( 69 ). Winston et al reported that incorporating optic nerve radiography during anterior temporal lobectomy (ATLR) for refractory temporal lobe epilepsy (TLE) had the potential to reduce the severity of postoperative VFDs without impacting seizure outcomes or hippocampal resection ( 70 ).…”
Section: Resultsmentioning
confidence: 99%